Acquiring a novel coordination skill without practicing the correct motor commands - Feijen, L.; Hodges, N. J.; Beek, P. J. (Journal of Motor Behavior, 2010)
There is evidence that experience of the sensory consequences, in the absence of practice of the required motor commands, is sufficient to learn new bimanual coordination patterns. This was shown through improvements of an incongruent group who practiced a desired 30° phase offset between the limbs while 1 limb was weighted such that the desired phase relation was achieved when synchronous motor commands were sent to the limbs (P. Atchy-Delama, P. G. Zanone, C. E. Peper, & P. J. Beek, 2005). In addition to testing a similar incongruent and congruent group (i.e., no weight), the authors extended this experiment by removing visual feedback during practice and by including an auditory modeling and passive guidance group. All groups showed improvement, except for the modeling group. The passive guidance group made more errors in posttests than the congruent and incongruent groups. Only the congruent group increased the amount of time around 30° after practice. Active experience of the sensory consequences combined with practice sending appropriate motor commands is the most effective method for learning, even though strategic improvements can be attained without experience of the latter.